Information-seeking behaviours in Australian sexual minority men engaged in chemsex. (December 2022) - Demant, Daniel; Carroll, Julie-Anne; Saliba, Bernard; Bourne, Adam
Highlights: Participants engaged in chemsex over long periods of time and on a regular basis. Most know where to seek professional help and access harm reduction information. Many worry about being judged by health professionals and few seek out assistance. Participants feel uncomfortable discussing chemsex with most health professionals. Information from sexual health professionals is trusted the most. Abstract: Introduction: Chemsex refers to using illicit substances to facilitate sexual experiences in men who have sex with men. Chemsex has been linked to significant negative impacts on psychological, social, and physical wellbeing. Little is known about information-seeking behaviours in this population. This study aims to provide an in-depth understanding of seeking and engaging with health information. Methods: Self-identified Australian sexual minority men who engage in chemsex (N = 184) participated in an anonymous cross-sectional survey. Variables included chemsex engagement, knowledge, perception and use of harm-reduction information, and associated health and support services. Pearson correlation and ANOVAs were conducted. Wilcoxon-Signed-Rank and Friedman tests were applied to analyse the perceived trustworthiness of information sources. Results: Chemsex represented a meaningful part of sexual events. Most participants knew where to access professional help and harm-reduction information but worried about being judged. Most did not feel comfortable discussing chemsex with health professionals except with sexual health doctors/counsellors. Few users discussed health risks with a professional. Information on chemsex was received through multiple sources with significant differences in perceived relevance and trustworthiness, with sexual health doctors/nurses ranked the most trustworthy information. Interest in non-traditional sources of information was low except for formal peer networks and anonymous personal expert advice. Conclusion: Engagement with health professionals and harm-reduction information is limited in this population, despite high risk and potentially significant adverse health outcomes. Results suggest that new and combined approaches are necessary to reach this population, including peer support networks, anonymous personal advice and changing community attitudes towards chemsex.